Essential oils from the leaves of Ocimum Basilicum L., Persicaria Odorata and Coriandrum Sativum L. in Malaysia: antiurolithic activity study based on Calcium Oxalate Crystallisation - Mat Shaari, Nurul Elyni; Susanti, Deny; Abd Hamid, Shafida (UiTM Press, 2021)
Calcium oxalate is one of the most common components in urolithiasis. Its treatment includes the use of synthetic drugs, ultrasound and surgery. However, cheaper alternative treatment using herbal medicine with less adverse side effect is preferred. Essential oils from Thai basil (Ocimum bacilicum L.), Vietnamese coriander (Persicaria odorata) and Chinese parsley (Coriandum sativum L.) were extracted and investigated for antiurolithic activity based on calcium oxalate crystallisation. Most of the crystals formed in control sample were hexagonal calcium oxalate monohydrate with sizes ranging between 3 to 4 m. The size of the crystals was found to be slightly reduced in O. bacilicum oil (2-4 m) at high concentration with less aggregation of crystals. Samples with P. odorata oil gave smaller crystal size (3 m) mainly in dehydrate form and the oil was also found to inhibit the aggregation of the crystals at high concentration. C. sativum oil enhanced crystallisation (5-6 m) with increased concentration and showed high aggregation of the crystals. This preliminary study shows the therapeutic potential of these medicinal plants to be used in traditional anti-urolithic therapy.